Neurological manifestations of falciparum malaria. - Newton, C; Warrell, D (1998)
Plasmodium falciparum remains one of the most common causes of central nervous system infection worldwide. Recently, differences between the pathophysiology of cerebral malaria in African children and nonimmune adults have been discovered, new syndromes occurring after malaria infection described, and mechanisms for the pathogenesis proposed. In addition, new antimalarial agents have been examined worldwide and initial studies on supportive studies conducted. This paper reviews these new advances, putting them into the perspective of the more established knowledge.